Infrared microspectroscopic chemical imaging applied to individual starch granules and starch dominant solid mixtures - Boatwright, Mark Daniel (Kansas State University, 2012)
Chemical imaging enables displaying the distribution of different substances within a field of view based on their fundamental vibrational frequencies. Mid-IR bands are generally strong and feature direct correlation to chemical structure, while near IR spectra consist of overtones and combinations of mid-IR bands. Recently, mid-IR microspectroscopy has enabled determination of the relative substitution of hydroxyl groups with the modifying agent for individual waxy maize starch granules by using synchrotron source. The brightness and non-divergence of the synchrotron source and confocal masking enabled obtaining individual spectra with 5 [mu]m[superscript]2 masking and 1 [mu]m raster scanned steps. Each 1 [mu]m step results from the coaddition of hundreds of scans and lengthy data collection is required to produce data. The recent breakthrough at the Synchrotron Research Center uses a multi-beam synchrotron source combined with a focal plane array microspectrometer. This major improvement in localized detection of the modifying agent within single waxy maize starch granules is the increased efficiency of focal plane array detection and an effective spatial resolution of 0.54 [mu]m. Mixtures of granular solids represent an analytical challenge due to the range of heterogeneity and homogeneity within samples. Near IR imaging provides deeper sample penetration allowing for solid mixture analysis. However, the broad, overlapping bands present in the near IR necessitates statistical data treatment. This requires imaging specimens representative of the individual components to create spectral libraries for classification of each component. Partial least squares analysis then allows characterization and subsequent pixel analysis provides quantitative results. The primary break system for wheat milling was studied as it is key in releasing endosperm to be further ground into fine flour in subsequent processes. The mass balance of endosperm throughout individual unit processes was determined by obtaining flow rates of incoming and outgoing millstreams and calculating endosperm content through pixel identification. The feed milling industry requires the use of a tracer to determine adequate mixing and mix uniformity to limit the time and energy in processing. Near IR imaging allows individual components of a formula feed to serve as a self-tracer, eliminating the need of an inorganic tracer.
Keywords: Chemical imaging; Focal plane array; Modified starch; Flour milling; Mixing uniformity; Analytical Chemistry (0486); Chemistry, Agricultural (0749)